SUSTAINABLE FISHERY MANAGEMENT: LEARNING FROM THE INDIGENOUS COMMUNITY OF BIAK - Arni Putri Awaliyah Umar; Doddy Aditya Iskandar (Sean Institute, 2023)
The depletion of natural resources has occurred worldwide, especially in the field of fisheries. Various solutions to address this depletion involve the conservation or preservation of natural resources. The management carried out by indigenous communities is considered one of the important environmental governance approaches to protect ecosystems and natural resources. Understanding the fundamental principles of how local actors can collaborate successfully in environmental governance can provide valuable insights into how ecosystems and natural resources are managed by them and how the provision of related ecosystem services can be sustained. This research utilizes the design principles proposed by Ostrom to identify the resource management conducted by the Biak Indigenous Community in the Biak Numfor Regency through the Sasisen practices rooted in local knowledge. Sasisen practices are assessed as a contributing factor to natural resource preservation. The aim of this research is to analyze the existence of each principle and how they are applied. The analysis is based on data collected through interviews with various local actors. These principles help explain how indigenous communities can organize collective actions in the management of natural resources. There are Ostrom principles verified by these Sasisen practices, namely the principles of boundaries, rules, collective choice, monitoring, and graduated sanctions. As for the principles of recognition of rights and nested enterprises, conflicts persist between indigenous communities and government agencies, as well as between small-scale and large-scale fisheries sectors. This research also explains the behavior of indigenous communities in preserving their fisheries resources, which can be considered by the government.